Nuremberg Trials (Harvard Law School Library's Nuremberg Trials Project)
The Harvard Law School Library's Nuremberg Trials Project is an open-access initiative to create and present digitized images and full-text versions of the Library's Nuremberg Trials documents, descriptions of each document, and general information about the trials. The project provides access to the documentary record and other associated materials for all thirteen trials. We currently offer page images and searchable document descriptions for all documents as well as searchable full-text versions for most prosecution exhibits and most of the trial transcripts. Both prosecution and trial exhibits as well as all trial transcripts are currently only offered in the English-language versions used at the time of the Trials. Important: when citing from documents and transcripts, always verify the exact wording by consulting the accompanying page images of the document in question. The full-text versions of transcripts and documents are a product of human- and computer-aided transcription and may deviate in small ways from the originals.
Keywords: _open access

The Royal Mint Museum
The Royal Mint Museum contains a valuable numismatic library of some 15,000 volumes. This includes archival material acquired in large part from departments of the old Royal Mint at Tower Hill, such as the Engraving Department, the Die Office and the Pyx Office. For the most part this material dates back to the beginning of the 20th century and in its day-by-day character is a useful adjunct to the official files in The National Archives and to the published Annual Reports of the Royal Mint.

Looking at Nuclear Weapons by Type: Introducing the Nuclear Weapon Systems Project - Facini, Andrew (The Council on Strategic Risks, 2023)
Diving into CSR's launch of a clear, concise repository of deployed nuclear weapons across their history.
Keywords: _open access

Houston Mutiny and Riot Records (South Texas College of Law Houston Digital Collections)
Keywords: _open access

Affiches de guerre - Calypso
La collection d’affiches de guerre des bibliothèques de l’Université de Montréal se compose de plus de 3000 images produites au cours des deux guerres mondiales ainsi que de l’entre-deux-guerres. Chaque affiche a été numérisée et son contenu a fait l’objet d’une description détaillée.
Keywords: _open access